The viability status and level of compitativeness of tobacco Industry in peninsular Malaysia / Ahmad Fauzi Puasa, Ismariah Ahmad and Ismail Ahmad - Puasa, Ahmad Fauzi; Ahmad, Ismariah; Ahmad, Ismail (Universiti Teknologi MARA Cawangan Pahang, 2003)
The main intention of this paper is to evaluate the viability status and the competitiveness of the tobacco industry in Peninsular Malaysia. There are two methods of analysis has been adopted encompasses of i) financial analysis to find out how feasible tobacco farming activity from different type of farming options and ii) competitive analysis using break-even point concept to find out the level of competitiveness. This financial analysis uses current price data to reflect the performance of the different types of tobacco farming activities. Its role of discipline in the project analysis is mainly towards diagnosing weakness in the existing system and to recommending action for further consideration. Financial analysis is based on the information from the cash flow budget for any project. Using the cash flow data, the break-even analysis will be computed so that any change in tobacco price will affect the whole tobacco farming activities budget. The data from Kelantan and Terengganu has been used for this study. These two states are two major tobacco producing areas in Peninsular Malaysia, comprising 14,615 ha or 92.7% of the total area in the Peninsular Malaysia. There are three types of tobacco farming techniques. Firstly farmers plant only tobacco and sell wet tobacco leaves to curers. Secondly farmers plant tobacco as well as curing the leaves. Thirdly farmers only cure the leaves. Each of these tobacco-farming activities has its own entity of individual operational cash flows for running the business. This study develops individual cash flow for financial analysis in order to examine viability of the farming activities. The viability of this financial analysis is based on the net present value and internal rate of return for each type of the farming activities. The break-even analysis will be computed in order to know the break-even price for each of the farming group. The results from this financial analysis will reflect the viability of the tobacco industry according to the farming activities and the break-even analysis will determine the level of competitiveness of the tobacco industry in Peninsular Malaysia